The clinical value of inflammatory factors in evaluating the prognosis of patients with acute myeloid leukemia: Inflammatory Factors in AML Prognosis - Li, Jianghuizi; Liu, Feng; Wu, Wen (Journal of Medical Biochemistry, 2025)
Background: To assess the importance of inflammatory factors in predicting outcomes in individuals diagnosed with acute myeloid leukemia.Methods: Between July 2017 and  December 2019, a total of 100 patients with a recent diagnosis of acute myeloid leukemia (AML) were recruited from the Hematology Department of our hospital’s Cancer Center and assigned to the AML group. Additionally, 60 individuals with no underlying health conditions who underwent standard medical checkups during the same period were selected as the control group. Serum levels of IL-2, IL-4, IL-17A, TNF-α, IFN-γ, and LIF were measured through ELISA. All participants in the AML group were followed up for three years. Based on the European Leukemia Network (ELN) genetic risk stratification criteria, patients were categorized into favorable, intermediate, and adverse prognosis subgroups. Inflammatory marker profiles were then compared among these subgroups. Results: Compared to healthy individuals, the AML group presented significantly increased serum concentrations of IL-4, IL-17A, and TNF-α, while levels of IL-2, IFN-γ, and LIF were significantly decreased (P < 0.05). Upon stratifying patients by prognostic classification, those in the favorable and intermediate prognosis categories exhibited notably lower IL-4, IL-17A, and TNF-α levels relative to the poor prognosis group (all P < 0.05). In contrast, levels of IL-2, IFN-γ, and LIF were notably elevated in the subgroup with favorable prognostic profiles (all P < 0.05). Additional analysis of cytokine expression indicated that increased levels of IL-4, IL-17A, and TNF-α were linked to worse 3-year survival performance (P < 0.05). Conversely, higher expression of IL-2, IFN-γ, and LIF was significantly associated with better long-term survival outcomes relative to patients with reduced expression levels (P < 0.05).Conclusion: The abnormal levels of IL-4, IL-17A, TNF-a, IFNγ and LIF in patients with acute myeloid leukemia are increased, while the abnormal levels of IL-2, IFNγ and LIF are decreased, which has certain guiding effect on prognosis assessment and can be used as auxiliary indicators for prognosis assessment of AML.
Keywords: acute myeloid leukemia; Prognosis; TNF- a; LIF; IFNγ; IL-2; IL-4; IL-17A